Tracheoesophageal fistula associated with paracoccidioidomicosis - Antonio Carlos Nogueira; Daniel Soares de Sousa Dantas; Francisco Garcia Soriano; Simone Peres Pilli; João Epalanga Júnior Vidro; Edmar Tafner; Lincoln Tavares de Andrade; Luis Masuo Maruta; Hélio Minamoto; José Pinhata Otoch; João Augusto dos Santos Martines (University of São Paulo, 2011)
Paracoccidioidomycosis is a systemic fungal disease caused by Paracoccidioides brasiliensis, agent geographically distributed to certain areas of Central and South America. The infection by P. brasiliensis has been reported from north Mexico to south Argentina. Paracoccidioidomycosis presents similar clinical findings of many other diseases whatever in acute or chronic scenarios. Chronic pulmonary paracoccidioidomycosis is frequently misdiagnosed as malignancy or tuberculosis. The authors present a case of a 57 year-old man admitted to the hospital due to a chronic consumptive syndrome. He underwent anti-tuberculous treatment with rifampin, isoniazid and pyrazinamide 1 year ago without resolution of the simptoms. During the clinical investigation, pulmonary paracoccidioidomycosis with tracheoesophageal fistula was diagnosed. The systemic infection was treated with deoxicolate B amphotericin followed by sulfametoxazole and trimetoprin due to acute renal function impairment. The fistula was endoscopically treated; inittialy with the protection of left main bronchus with a tracheal prosthesis followed by the esophageal fistula's ostium clipping.